The world economy : global trade policy 2010 - Greenaway, David (World economy (Malden, Mass.), 2011)
This is the seventeenth volume in an annual series in which leading economists provide a concise and accessible evaluation of major developments in trade and trade policy. Examines key issues pertinent to the multinational trading system, as well as regional trade arrangements and policy developments at the national levelProvides up-to-date assessments of the World Trade Organization's current Trade Policy ReviewsA vital resource for researchers, analysts and policy-advisors interested in trade policy and other open economy issues Analyses global trade policy in Turkey, China and The Dominican.